If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.3 = x Solving 2.3 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2.3 + -1x = x + -1x Combine like terms: x + -1x = 0 2.3 + -1x = 0 Add '-2.3' to each side of the equation. 2.3 + -2.3 + -1x = 0 + -2.3 Combine like terms: 2.3 + -2.3 = 0.0 0.0 + -1x = 0 + -2.3 -1x = 0 + -2.3 Combine like terms: 0 + -2.3 = -2.3 -1x = -2.3 Divide each side by '-1'. x = 2.3 Simplifying x = 2.3
| (3x^2)+(10x)=16 | | 3x-6+10x=7x-4 | | 3x-18+90-x=180 | | (x+3)-81=0 | | 3x-15+2x+30=180 | | x+3-81=0 | | 8x^2-18x+106=0 | | 3x+26=-1 | | (9x^2)+(30x)=144 | | (3x^2)+(10x)=144 | | (-2x^3)(-2x^2)= | | 12m+10n-21=0 | | (-2a^3*1b^2)(-2a^2*1b^3)= | | 4x^2+8x-1=0 | | 0.7x^2+3.7x+1=0 | | 5X^2-32X+36=0 | | N-26=9 | | 26-n=9 | | 12x-4=4x+4 | | 1.5n=75 | | y=-7x+1 | | m-1.8=6 | | 6x+1=4x+3 | | 81=3n | | 0.9-x=1 | | x^3+18x^2+71x+40=0 | | u^2-u-7=0 | | -14=7x | | -15=-5x | | 4X^3-18X^2+16X+3=0 | | -8=x+12 | | 20+8q=-42 |